The Solvability and Numerical Simulation for the Elastic Beam Problems with Nonlinear Boundary Conditions - Qun Gao (Abstract and Applied Analysis)
We study the existence of multiple solutions for a fourth-order nonlinear boundary value problem. We give some new criteria for guaranteeing that the fourth-order elastic beam equation with a perturbed term has at least three solutions. The proof is based on some three critical points theorems of B. Ricceri. Furthermore, numerical simulations are also presented.